A review of the molecular mechanism of apoptosis and its role in pathological conditions - AMAR PREET KAUR,; SANDEEP AGRAWAL, (International Journal of Pharma and Bio Sciences, 2019)
Apoptosis is a type of programmed cell death common to all multicellular organisms. It is a physiological process responsible for elimination of unwanted, excessive, worn out and damaged cells. Apoptosis can be triggered by a variety of intracellular stimuli which initiate intrinsic pathway while engagement of death receptors on cell surface triggers an extrinsic apoptotic pathway. Apoptotic cells share distinct morphological features including cell shrinkage, nuclear fragmentation and formation of apoptotic bodies which contain parts of nucleus and cytoplasm. Apoptotic bodies are engulfed by phagocytes within a very short period of time without provoking any inflammatory response. Role of mitochondrial protein cytochrome ‘c’ and cysteine proteases called ‘caspases’ are well defined in the mechanism of apoptotic pathways. Apoptosis is a highly regulated pathway which is indispensable for maintenance of homeostasis during embryonic as well as adult life of an organism. Regulation of apoptosis is brought about by multiple molecules including Bcl-2 family of proteins and inhibitor of apoptosis proteins (IAPs). Although apoptosis is a physiological phenomenon, failure in its regulation machinery might lead to too much or too little of cell death culminating in various pathological conditions including cancer, AIDS, autoimmune and neurodegenerative diseases. Understanding the molecular mechanism of apoptosis including multiple genes, proteins, death receptors, death signals and various other components of signaling pathways will provide new insights in developing strategies to regulate the cell death and to formulate new therapeutic targets. This review covers the current knowledge on the molecular events of apoptotic cell death and their significance in health and disease.